Traditional markets and diversity of edible plant trading: Case study in Ujung Berung, Bandung, West Java, Indonesia - BUDIAWATI SUPANGKAT ISKANDAR; JOHAN ISKANDAR; BUDI IRAWAN; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2018)
Iskandar BS, Iskandar J, Irawan B, Partasasmita R. 2018. Traditional markets and diversity of edible plant trading: Case study in Ujung Berung, Bandung, West Java, Indonesia. Biodiversitas 19: 437-452. Traditional markets are where traders and buyers meet; places where the supply and demand activities of selling and buying between traders and buyers occur. Buying and selling activities are realized based on the practice of bargaining, made possible by a negotiated willingness to slide a price. In bargaining, social relationships are activated. Traditional markets are managed by local companies called PD Pasar. The traders are generally small business groups. A particular feature of traditional markets is that they are primarily places to trade various foodstuffs that are needed by urban dwellers, including products such as rice and other additional staple foods, vegetables, spices and fruits. The aim of the study reported here was to detail various edible plant species and their variations (landraces) that are the source of products traded in a typical traditional market of West Java, Indonesia. The products of interest to us included carbohydrate staple foods, vegetables, spices, and fruits, produced by village farmers. We investigated the trading network for these edible plant commodities; and the role of traditional markets in supporting the conservation of biodiversity in the edible plants traded. The method used in this study was qualitative, applying an ethnobotanical approach. Field techniques of direct observation, participant observation and deep interview were applied. The results of the study showed that the traditional market of Ujung Berung, in Bandung, West Java, plays an important role in trading various edible plants produced by village farmers. Altogether, 120 plant species were recorded in the market, out of a total of 188 variants (species, and intra-species landraces), representing 44 families. There were 103 species that provided vegetables, 58 species used as spices, 39 species used for their fruits, and 10 that provided carbohydrate staple foods. In general, these plants commodities traded in the Ujung Berung traditional market are supplied by village traders or are bought from the central market in Bandung. The traditional market of Ujung Berung, Bandung has an important role as a place of economic activity for small businesses Furthermore, it is a factor supporting biodiversity in the edible plants traded.